(untitled) (Bioresearch Communications, 2022)
The present study was mainly aimed at exploring the causal association of the atherogenic (ApoB) and antiatherogenic apolipoproteins (ApoA1) and their ratio in the basic defects of pancreatic β cell dysfunction and insulin resistance in type 2 Diabetes Mellitus (T2DM). An intermediate stage towards diabetes, the prediabetic stage, was chosen to explore the association. Following a standardized selection process, 131 subjects were purposefully recruited for the study, including 18 with impaired fasting glucose (IFG), 56 with impaired glucose tolerance (IGT), and 57 with type 2 diabetes (T2DM). Fifty-nine healthy subjects served as controls. Glucose, lipid and insulin were estimated by glucose-oxidase, enzymatic colorimetric assay and enzyme linked immunosorbent assay (ELISA) respectively. Serum ApoB and ApoA1 were estimated by immuno-nephelometric method. Appropriate statistical tools were used to calculate statistical differences using Statistical Package for Social studies (SPSS) for Windows V12. Absolute insulin (mIU) levels were significantly higher in the IGT and T2DM groups compared to controls (p 0.001 and p = 0.001, respectively). HOMA%B (meanSD) was significantly lower in T2DM groups (p=<0.001) and higher in IGT compared to the controls although it is significantly lower in IFG compared to the controls but mean value is about 90%. HOMA%S was significantly lower in IGT and T2DM group (p=0.001 and 0.002 respectively). ApoA1 levels were significantly higher only in the T2DM group (p = 0.027), whereas ApoB levels were higher in both the IGT and T2DM groups (p = 0.026-0.001).. Neither ApoB nor ApoA1 showed any significant difference in the IFG group as compared to control. ApoB-ApoA1 ratio did not show significant difference among the groups. ApoB showed significant positive correlation with both fasting and postprandial glucose (p=0.006 and 0.040 respectively). In IGT group ApoB was positively correlated with absolute insulin (p=0.025) and HOMA%B (p=0.049) and negatively with HOMA%S (p=0.026). ApoB, but not ApoA1 or the ApoB and ApoA1 ratio, seem to have a causal association with insulin resistance, and elevation of ApoB is also modulated by obesity and atherogenic lipids. Bioresearch Commu. 9(1): 1170-1176, 2023 (January)